Investigation of Differences in P53 Gene Polymorphisms between Schizophrenia and Lung Cancer Patients in the Turkish Population - Ozbey, Ulku; Yuce, Huseyin; Namli, Mustafa; Elkiran, Tamer (Hindawi Ltd, 2011)
Objective. The reduced incidence of cancer observed in schizophrenia patients may be related to differences in genetic background. It has been suggested that genetic predisposition towards schizophrenia is associated with reduced vulnerability to lung cancer, and p53 gene is one of the candidate genes. In our study, we aimed to investigate polymorphisms in the BstUI in exon 4 and MspI in intron 6 restriction sites of the p53 gene in Turkish schizophrenia patients, lung cancer patients, and controls. Material and Methods. Allele and genotype incidence of these polymorphisms with their haplotype combinations were studied in 100 Turkish lung cancer and schizophrenia patients and 100 controls without malignant and schizophrenia diseases. The genotype characteristics were determined by PCR-based RFLP method using DNA extracted from peripheral blood. Results. For the BstUI and MspI polymorphism, there were found significant differences in the genotype and allele frequencies between schizophrenia and lung cancer patients with control groups (P < .01). The analysis based on haplotype frequencies showed the presence of BstUI-MspI 2-1 haplotype in cancer patients (12%) in contrast to the absence of this haplotype in schizophrenia and controls. Only in lung cancer patients we found both significant decrease of A1 allele of the p53 codon 72 (OR0.23, 95% CI 0.9-0.58) and A1/A1 homozygous genotype (P < .0001, OR0.19). Conclusion. The results of this study suggest a protective effect of A1 allele against lung cancer, and the p53 MspI polymorphism may modify the susceptibility to lung cancer as a single factor rather than in combination with BstUI polymorphism.
Keywords: Codon 72 Polymorphism; Germ-Line Polymorphisms; Tumor-Suppressor Gene; Clinical-Implications; Haplotypes; Smoking; Susceptibility; Association; Risk